Educational Management to Promote Inclusive Environments in Costa Rica: An Analysis from an Educational Policy Perspective - Chen-Quesada, Evelyn (2023)
The educational management implemented by principals is essential to guarantee compliance with educational policies, which are not only an obligation but a conviction in schools wanting to promote inclusive environments and respect for diversity, multiculturalism, comprehensive training, teamwork, creative capacity, abstract thinking, and social entrepreneurship through equitable and accessible coexistence spaces. Therefore, this study aims to analyze the fulfillment of the educational policy on inclusive education from the perspective of educational management. The research implemented a qualitative approach, with the participation of six primary school principals in Costa Rica and used the case study technique through a semi-structured interview. The findings show the existence of situations limiting the application of educational policies, mainly in the promotion of inclusive environments oriented to prejudice-free coexistence respecting diversity, as well as in issues of lifelong learning and institutional transformation as part of the orientations of the country’s public policy in education.